Prognostic value of aldo-keto reductase family 1 member B10 (AKR1B10) in digestive system cancers: A meta-analysis - Liu, Rongqiang (Medicine (Baltimore), 2021)
BACKGROUND: Numbers of studies have reported that the expression of aldo-keto reductase family 1 member B10 (AKR1B10) is abnormal in digestive system cancers, and could be used as a prognostic biomarker. However, the results are argued. Therefore, we conduct a meta-analysis to comprehensively evaluate the prognostic value of high AKR1B10 expression for overall survival (OS), disease specific survival (DSS), and disease-free survival/recurrence-free survival (DFS/PFS) in digestive system cancers. METHODS: Hazard ratios (HRs) with its 95% confidence intervals (CIs) were calculated to assess the prognostic value of AKR1B10 by using the random effects model. The STATA version 12.0 software were used to perform all the analyses. RESULTS: Eleven articles including 1428 patients involved in this meta-analysis. The pooled analysis suggested that high AKR1B10 expression was not associated with OS (HR: 1.18; 95% CI: 0.69–2.00) and DFS/PFS (HR: 1.08, 95% CI: 0.67–1.76) in digestive system cancers. However, Further analysis revealed that high AKR1B10 expression indicated poor OS in oral squamous cell carcinomas (OSCC) (HR: 2.92, 95% CI: 1.86–4.58) and favorable DSS in hepatocellular carcinoma (HCC) (HR: 0.71, 95% CI: 0.52–0.97). CONCLUSIONS: The prognostic value of high AKR1B10 expression varied in different types of digestive system cancers. Further studies exploring the prognostic role of AKR1B10 in digestive system cancers are needed.